Falconer's Revolutionary Imprudence. Issue 2 (26th March 2015) - Biggar, Nigel
Abstract : While well intentioned, Lord Falconer's Assisted Dying Bill is imprudent in its enlightenment confidence that the legal prescription of procedural and institutional safeguards would be effective in preventing the abusive manipulation of vulnerable people into choosing assistance in suicide. Indeed, the Bill does not even meet the 'essential' conditions prescribed by Falconer's own Demos Commission. 1 Further, there is good reason to doubt that the proposed restriction of eligibility to the terminally ill would long survive the weakness of its own logic and the media's publicity of cases of the poignant suffering of the chronically ill and severely disabled.